Studies on Iberian Peninsula ultramafic flora: a selected nickel accumulation screening - Rufo Nieto, Lourdes; Fuente García, Vicenta de la; Sánchez-Mata, Daniel; Rodriguez-Rojo, Maria del Pilar (Lazaroa, 2004)
A complete list of taxa from southem Iberian Peninsula ultramafics were screened for Ni accumulation. All the studied specimens were collected by the Spanish botanist Prof. Salvador Rivas Goday and are preserved in the MAF Herbarium (Facultad de Farmacia, Universidad Complutense, Madrid). The study was carried out by a semi-quantitative chemical test. Only two species of the almost two hundred tested had a positive reaction: Alyssum serpyllifolium subsp. malacitanum Rivas Goday ex G. López (Brassicaceae) and Saxifraga gemmulosa Boiss. (Saxifragaceae).